Metabolic plasticity in blast crisis-chronic myeloid leukaemia cells under hypoxia reduces the cytotoxic potency of drugs targeting mitochondria - Luciana S. Salaverry; Tomás Lombardo; María C. Cabral-Lorenzo; Martin L. Gil-Folgar; Estela B. Rey-Roldán; Laura I. Kornblihtt; Guillermo A. Blanco (Discover Oncology, 2022)
Abstract Metabolic reprogramming (MR) influences progression of chronic myeloid leukaemia (CML) to blast crisis (BC), but metabolic programs may change transiently in a second dimension (metabolic plasticity, MP), driven by environments as hypoxia, affecting cytotoxic potency (CPot) of drugs targeting mitochondria or mitochondria-related cell stress responses (MRCSR) such as mitophagy and mitochondrial biogenesis. We assessed mitochondrial membrane potential (MMP), mitochondrial mass (MM), apoptosis, glucose uptake (GU), and CPot of arsenic trioxide (ATO), CCCP, valproic acid (VPA), vincristine (VCR), Mdivi1, and dichloroacetic acid (DCA) in CML BC cells K562 (BC-K562) under hypoxia through flow cytometry, and gene expression from GEO database. About 60% of untreated cells were killed after 72 h under hypoxia, but paradoxically, all drugs but ATO rescued cells and increased survival rates to almost 90%. Blocking mitophagy either with VCR or Mdivi1, or increasing mitochondrial biogenesis with VPA enhanced cell-survival with increased MM. DCA increased MM and rescued cells in spite of its role in activating pyruvate dehydrogenase and Krebs cycle. Cells rescued by DCA, VPA and CCCP showed decreased GU. ATO showed equal CPot in hypoxia and normoxia. MP was evidenced by differential expression of genes (DEG) under hypoxia related to Krebs cycle, lipid synthesis, cholesterol homeostasis, mitophagy, and mitochondrial biogenesis (GSE144527). A 25-gene MP-signature of BC-K562 cells under hypoxia identified BC cases among 113 transcriptomes from CML patients (GSE4170). We concluded that hypoxic environment drove a MP change evidenced by DEG that was reflected in a paradoxical pro-survival, instead of cytotoxic, effect of drugs targeting mitochondria and MRCSR.